Nilai-nilai Pendidikan Islam yang Terdapat dalam Tafsir Al Azhar Karangan Prof. Dr. Hamka Surat Al Baqarah Ayat 1-5 - Anggrainy, Nisa; Husni, Arman; Charles, Charles; Junaidi, Junaidi (Indonesian Research Journal on Education, 2023)
This study aims to determine the educational values of aqidah contained in the interpretation of Al Azhar by Prof. Dr. Hamka Surah Al Baqarah verses 1-5. The research method in writing this thesis uses library research, which is a study used to collect information and data with the help of various materials in the library such as documents, books, magazines, historical stories and so on. The sources of data used are primary data in the form of Hamka's Al Azhar commentary book and secondary data, namely books, journals, articles, and previous theses. The data collection technique in this research is documentation. The results of research on the values of Islamic education in the interpretation of Al Azhar by Prof. Dr. Hamka Surah Al Baqarah verses 1-5 which is about the value of faith education. Aqidah is something that is believed and held firmly. The main points of Islamic aqidah are summarized in the pillars of faith, namely belief in Allah, belief in angels, belief in Allah's books, belief in Allah's Apostle, belief in the last day and belief in qada and qadar. In the interpretation of Al Azhar by Prof. Dr. Hamka Surah Al Baqarah verses 1-5 only discusses some of the pillars of faith, namely in verse 1 it says that the letters contained at the beginning of the letter are extraordinary sentences that can be reached by people who are pious. Verses 2 to 4 explain the characteristics of a pious person, namely believing in Allah, believing in Allah's books, believing in the unseen. Belief in Allah can be proven by establishing prayer and donating some of the sustenance you have. Whereas verse 5 says if the above-mentioned qualities of piety are in a person, then he is very lucky.